1993
DOI: 10.1128/iai.61.1.8-12.1993
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pH and osmolality on in vitro phagocytosis and killing by neutrophils in urine

Abstract: Phagocytosis and intracellular killing of two strains ofEscherichia coli and a Staphylococcus saprophyticus by polymorphonuclear neutrophils (PMN) in pooled sterile urine at three osmolalities (800, 485, and 200 mosMlkg of H20) between pHs 5 and 8 was investigated. Urine at 800 mosM virtually abolished phagocytosis of both E. coli strains, regardless of pH, and reduced the phagocytosis of S. saprophyticus to 30%; no killing of any organisms took place at this osmolality. On the other hand, phagocytosis was as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Hence, the question arises why control of C. albicans growth is only affected in the brain and in the kidney which are, also under “normal” circumstances, the most affected organs during systemic candidiasis 37 . Failure of fungal clearance might relate to organ-specific factors that impair neutrophil function, such as the high osmolarity and urea content of renal tubules, or, for example, to the induction of regulatory responses 33 40 . Indeed, hyphal forms of C. albicans , which are only found in the kidney (but not in the spleen or in the liver), are more resistant to killing by phagocytes than yeasts and too large to be ingested by neutrophils, which instead degranulate and release oxidative contents extracellularly thereby contributing to tissue damage 33 .…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the question arises why control of C. albicans growth is only affected in the brain and in the kidney which are, also under “normal” circumstances, the most affected organs during systemic candidiasis 37 . Failure of fungal clearance might relate to organ-specific factors that impair neutrophil function, such as the high osmolarity and urea content of renal tubules, or, for example, to the induction of regulatory responses 33 40 . Indeed, hyphal forms of C. albicans , which are only found in the kidney (but not in the spleen or in the liver), are more resistant to killing by phagocytes than yeasts and too large to be ingested by neutrophils, which instead degranulate and release oxidative contents extracellularly thereby contributing to tissue damage 33 .…”
Section: Discussionmentioning
confidence: 99%
“…Collectively, these findings suggest a role for these environmental factors in susceptibility of wounds to infection. It was shown by Gargan et al 63 that neutrophil phagocytosis in urine was dependent on both osmolality and pH. Results revealed that phagocytosis by neutrophils was as good in urine as in Hanks balanced salt solution at both 485 and 200 mOsm at pH values between 6 and 8, whereas as at pH 5, phagocytosis of three bacterial strains was virtually abolished.…”
Section: Effect Of Ph On Polymorphonuclearcytes (Pmns)mentioning
confidence: 94%
“…Collectively, these findings suggest a role for these environmental factors in susceptibility of wounds to infection. It was shown by Gargan et al . that neutrophil phagocytosis in urine was dependent on both osmolality and pH.…”
Section: Effect Of Ph On the Immunological Responsementioning
confidence: 99%
“…Instead, the lack of efficient signals for rapid neutrophil recruitment in the kidney is associated with the inability of the organ to control fungal overgrowth and pseudohyphal formation [ 21 ]. In fact, the delayed neutrophil recruitment in the kidney at a time when Candida has already invaded within renal tubules could render the cells ineffective as neutrophils may have impaired effector function within the tubular urine microenvironment [ 82 , 83 ]. Therefore, defining the chemoattractant signals that are necessary for early protective neutrophil trafficking in Candida -infected tissues and elucidating why renal neutrophil recruitment is specifically sluggish are important directions for future research.…”
Section: Introductionmentioning
confidence: 99%